Agama dalam kajian sosiologi - Pur, Fatima Daeng Tiri (Maliki Interdisciplinary Journal, 2025)
This article examines religion from a sociological perspective as a central element in the social structure that shapes the patterns of human life. Religion is not only understood as a spiritual belief system but also as a tangible social phenomenon observable in daily interactions. Within this framework, religion functions as a source of values, norms, and ethics that regulate human behavior, while simultaneously serving as a medium of social cohesion that strengthens solidarity among individuals and groups. However, religion also has the potential to generate social conflict when diversity of beliefs is not accompanied by tolerance and mutual respect. The discussion covers several research methods in the sociology of religion, including descriptive, comparative, experimental, historical-comparative, and explanatory approaches. Moreover, it analyzes the influence of religion on social, cultural, political, and economic life, as well as its relation to mass media and interfaith interactions. The findings highlight the dual function of religion: first, as an integrative force that nurtures solidarity, peace, and stability; and second, as a factor that may intensify social divisions. Therefore, religion should be approached critically and empirically so that its role can genuinely contribute to building a harmonious, just, and civilized society.